DIFFERENTIATE FACTORS OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY OCCURRENCE IN BAJULMATI VILLAGE, WONGSOREJO DISTRICT, BANYUWANGI REGENCY 2019 - Moediarso, Bisyamsi Nawaijaya; Budiono, Perthdyatama Syifaq; Fatihuddin, Mohammad Fata; En, Theophilus Tan Zhu; Rantam, Berli Arfani; Gunawan, Ayu Liana; Diani, Masyithoh Wahyu; Mogi, Anjelina Kristina; Rahmi, Koyuki Atifa; Khoirunnisa, Auliai; Rarasati, Birgitta Vania; Purwati, Cincin Hari; Dewanti, Linda; Nuswantoro, Djohar (Journal of Community Medicine and Public Health Research, 2020)
Riskesdas result in 2013 showed that the prevalence of WUS population who were pregnant and at risk of CED was 24,2%. CED in pregnant women can cause abortion and premature birth, low birth weight babies and infant disability, children become malnourished and brain development is hampered, and children are at risk of developing metabolic diseases. In Bajulmati Village there were 15 pregnant women. 40% of 15 pregnant women suffer from CED. The purpose of this study was to determine differences between groups based on maternal age, maternal occupation, family income, previous pregnancy history, history of chronic illness, and maternal knowledge about nutrition in the incidence of pregnant women with CED in Bajulmati Wongsorejo Banyuwangi and differences in knowledge levels and attitudes towards behavior about nutrition after intervention. An observational analytic, cross sectional research design using questionnaires and observations. The sample selection technique uses total sampling technique. There were significant differences between groups based on family income in the incidence of CED in pregnant women and previous pregnancy history in the incidence of CED in pregnant women. Level of knowledge gained after the intervention was in the form of counseling to Prevent CED significantly.